Combined Magnesium/Polyethylene Glycol Facilitates the Neuroprotective Effects of Magnesium in Traumatic Brain Injury at a Reduced Magnesium Dose. (15th July 2016) - Busingye, Diana S.; Turner, Renée J.; Vink, Robert
Summary: Aims: While a number of studies have shown that free magnesium (Mg) decline is a feature of traumatic brain injury (TBI), poor central penetration of Mg has potentially limited clinical translation. This study examines whether polyethylene glycol (PEG) facilitates central penetration of Mg after TBI, increasing neuroprotection while simultaneously reducing the dose requirements for Mg. Methods: Rats were exposed to diffuse TBI and administered intravenous MgCl2 either alone (254 μ mol/kg or 25.4 μ mol/kg) or in combination with PEG (1 g/kg PEG) at 30‐min postinjury. Vehicle‐treated (saline or PEG) and sham animals served as controls. All animals were subsequently assessed for blood‐brain barrier permeability and edema at 5 h, and functional outcome for 1 week postinjury. Results: Optimal dose (254 μ mol/kg) MgCl2 or Mg PEG significantly improved all outcome parameters compared to vehicle or PEG controls. Intravenous administration of 10% MgCl2 alone (25.4 μ mol/kg) had no beneficial effect on any of the outcome parameters, whereas 10% Mg in PEG had the same beneficial effects as optimal dose Mg administration. Conclusion: Polyethylene glycol facilitates central penetration of Mg following TBI, reducing the concentration of Mg required to confer neuroprotection while simultaneously reducing the risks associated with high peripheral Mg concentration.